Perencanaan dan Simulasi Sistem Pendistribusian Kelistrikan Tegangan Rendah Kawasan Kampus III Universitas Islam Negeri Imam Bonjol Padang - Arzul Arzul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
The Campus III area of Imam Bonjol State Islamic University Padang is located in the Bangek River area, Balai Gadang Kec. Koto Tangah, Padang-West Sumatra, with an area of 39,000 m2. The Campus III area of Imam Bonjol State Islamic University, Padang consists of 8 lecture buildings which are divided into 2 electricity distribution zones. PLN (Persero), 20 kV medium voltage system. Each building has a panel that is supplied with electricity from a low voltage panel (PUTR). The distribution of the load for each building has different distances, some are near and far from the power source. The total power in the Campus III area of Imam Bonjol State Islamic University, Padang is 3,069.1 kVA with a TDL of PT. PLN (Persero) 3.465 kVA voltage 20 kV. The ground cable used is NYFGbY type with sizes 4x150mm2, 4x185mm2 and 4x240mm2. From the results of the calculation of the voltage drop from the existing data, the largest voltage drop was obtained at 155.13 volts or 40.82% and the smallest voltage drop was obtained at 2.58 volts or 0.67%. the largest voltage was obtained at 9.16 volts or 2.41% and the smallest voltage drop was obtained at 2.58 volts or 0.67%. From the results of the calculation of power losses with the data obtained, the results of power losses at 32,905.58 Watts (0.9%). While the calculation of power losses analysis results in 21,642.11 Watts (0.59%). From the simulation results of losses and voltage drop at ETAP 12.6, the highest voltage drop is on MDP 1-SDP L with a percentage of 4.34% and the value of losses is 10.7 kW and the lowest voltage drop is on MDP 1-SDP J with a percentage of 0.60% and the value of losses is 1.0 kW.